Defoliants and Desiccants - Frederick M. Fishel (EDIS, 2019)
This document discusses the meaning of the terms “defoliant and desiccant,” their patterns of use, and provides a listing of these products registered for use in Florida. This document is PI-101, one of a series of the Agronomy Department, UF/IFAS Extension. Original publication date February 2006.